Justifying violent protest: law and morality in democratic states - Greenwood-Reeves, James (Routledge, Taylor & Francis Group, 2023)
"This book presents a radical, but compelling, argument that liberal democracies must be able accommodate violent protest. We often think of violent protest as being alien to liberal democracy, an extraordinary occurrence within our peaceful societies. Yet this is simply untrue. Violent protest is a frequent and normal part of democratic life. The real question is: should it be? Can rebellion or riot against government ever be morally justifiable in our society? By framing state demands for obedience as 'legitimacy claims', or moral arguments, states who make illogical and unjust laws make weaker arguments for obedience. This in turn gives citizens stronger moral reasons to disobey. Violence can act as moral dialogue - with expressive and instrumental value in denouncing unjust laws - and can have just as important a role in democracy as peaceful protest. This book examines the activism of Hong Kong pro-democracy protesters, Extinction Rebellion, Black Lives Matter, and many other groups internationally, in order to demonstrate that not only can violent protest be acceptable; at times of grave injustice, it is unavoidable. This book will appeal to a broad range of academics, in legal and political theory, sociolegal studies, criminology, history and philosophy, as well as others with interests in contemporary forms of protest"--